One-dimensional simulation of a 4-stroke SI engine employing novel cylinder head concept : intake and exhaust flow investigation - Khairul Aizat, Abdul Rahim (2010)
This project investigates the flow characteristic in novel cylinder head at various port size and runner length. Novel cylinder head engine is a design engine that operates in a 4-stroke operational cycle. This engine uses a second opposed piston in designed cylinder head that moves at half the cyclical rate of the main piston, thus giving six piston movements per cycle. Functionally, the second piston replaces the valve mechanism of a conventional engine. Intake and exhaust poppet valve is replaced with two-stroke reed valve and exhaust port similar with two-stroke engine mechanism. The flow in a pipe of an engine exhaust and/or inlet system is treated as one dimensional. This means that the pressures, temperatures and flow velocities obtained from the solution of the gas dynamic equations represent mean values over the cross-section of the pipes. 1-d simulation tool used in this investigation is GT-power. Simulation runs with limitation of port size not exceed 70% size of cylinder head and exhaust length is limit to length of the motorcycle. The parameters investigated are volumetric efficiency of engine at difference engine speed and mean pistons speed. The parameter to investigate is flow rate during motoring only. The engine speed is limited to 4000 rpm related to maximum torque of original engine. Volumetric efficiency is increase with bigger intake port and smaller exhaust port. Elongations of the exhaust pipes give an improvement potential of the engine efficiency. The optimal value to choose in the novel cylinder head from the simulation result is at intake port size of 24 mm and exhaust port 16 mm as it has the optimal efficiency. For runner length the optimal value at intake runner length 90 mm and exhaust runner length 1050 mm.